PERAN AKUNTANSI DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS ORGANISASI: SYSTEMATIC LITERATURE REVIEW - Asri Ningsih Pertiwi; Semiwati Semiwati; All Ya Rusda Permatasari; Niken Widatiningsih; Nurung Nurung; Muhammad Jalaludin (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Transparency and accountability are fundamental principles in organizational governance that have received increasing attention due to rising stakeholder demands and the growing complexity of the organizational environment. Accounting plays a strategic role as an instrument for providing reliable financial information to support both principles, in both the public and private sectors. This study aims to comprehensively examine the role of accounting in enhancing organizational transparency and accountability through the Systematic Literature Review (SLR) approach. The research method follows the PRISMA 2020 guidelines by analyzing reputable scholarly articles published between 2015 and 2025. The selection process involved stages of identification, screening, eligibility, and inclusion, resulting in 18 articles that met the research criteria. The synthesis of the literature indicates that the implementation of accounting standards, such as IFRS and accrual-based Government Accounting Standards, consistently contributes positively to improving the quality of financial reporting, information disclosure, and organizational accountability mechanisms. In addition, the digitization of accounting and financial reporting systems strengthens oversight and increases information accessibility for stakeholders. However, the effectiveness of accounting's role still faces various challenges, particularly related to human resource competence, organizational culture, and technological infrastructure readiness. This study provides a theoretical contribution to the development of accounting-based governance research, as well as practical implications for organizations, regulators, and policymakers in strengthening transparency and accountability.